2013
DOI: 10.1007/s00253-013-5446-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of modular bifunctional processive endoglucanase Cel5 from Hahella chejuensis KCTC 2396

Abstract: Cel5 from marine Hahella chejuensis is composed of glycoside hydrolase family-5 (GH5) catalytic domain (CD) and two carbohydrate binding modules (CBM6-2). The enzyme was expressed in Escherichia coli and purified to homogeneity. The optimum endoglucanase and xylanase activities of recombinant Cel5 were observed at 65 °C, pH 6.5 and 55 °C, pH 5.5, respectively. It exhibited K m of 1.8 and 7.1 mg/ml for carboxymethyl cellulose and birchwood xylan, respectively. The addition of Ca(2+) greatly improved thermostabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 52 publications
1
29
1
Order By: Relevance
“…The enzyme cannot digest pNPG, which indicates that Egls has no β-glucanase activity. This result was in agreement with the findings that some cellulases from Bacillus showed both endoglucanase activity and exoglucanase activity Ghatge et al 2014;Wei et al 2015). Egls is very useful for the pretreatment of lignocellulose of biomass to produce reducing sugar that is used in bio-products and bioenergy production.…”
Section: Substrate Specificitysupporting
confidence: 82%
See 1 more Smart Citation
“…The enzyme cannot digest pNPG, which indicates that Egls has no β-glucanase activity. This result was in agreement with the findings that some cellulases from Bacillus showed both endoglucanase activity and exoglucanase activity Ghatge et al 2014;Wei et al 2015). Egls is very useful for the pretreatment of lignocellulose of biomass to produce reducing sugar that is used in bio-products and bioenergy production.…”
Section: Substrate Specificitysupporting
confidence: 82%
“…The value K m /K cat of Egls was calculated as 1.74 × 10 −2 mg/ml S. The kinetic parameters (K m , V max , and K cat ) of an endoglucanase from Bacillus strain were found as 0.25 mg/ml, 20 μmol/ml/min, and 0.55/S respectively ). The K m of endoglucanase from the strain Hahella chejuensis KCTC 2396 was 1.8 mg/ml (Ghatge et al 2014). The higher K m value of our strain indicated that the enzyme Egls is less efficient in digesting CMC substrate than reported strains.…”
Section: Kinetic Parameters K M /K Catmentioning
confidence: 68%
“…As far as is known, our current knowledge of the roles of CBMs in processivity of cellulases is mainly based on the comparison of modular cellulases comprising a catalytic domain and different CBMs with their CBMs-deleted variants or catalytic domain mutants [5,6,[22][23][24]. However, it is known that more than 60% of cellulases in cellulose-degrading organisms are non-modular proteins without CBMs [25].…”
Section: Introductionmentioning
confidence: 99%
“…Sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) was carried out to analyze protein purity on a vertical slab gel with 5 % (w/v) staking gel and 12 % (w/v) separating gel under denaturing condition. The purification of recombinant Cel5 was carried out as described previously (Ghatge et al 2014). …”
Section: Chemicals and Enzymesmentioning
confidence: 99%
“…Gel extraction and plasmid preparation kits were purchased from Qiagen (Valencia, CA, USA). The recombinant plasmid pECel5 (Ghatge et al 2014) was used for expression of endoglucanase Cel5 derived from H. chejuensis.…”
Section: Chemicals and Enzymesmentioning
confidence: 99%